Premise for Standardized Sepsis Models. Issue 1 (January 2019) - Remick, Daniel G.; Ayala, Alfred; Chaudry, Irshad H.; Coopersmith, Craig M.; Deutschman, Clifford; Hellman, Judith; Moldawer, Lyle; Osuchowski, Marcin F.
Abstract : ABSTRACT: Sepsis morbidity and mortality exacts a toll on patients and contributes significantly to healthcare costs. Preclinical models of sepsis have been used to study disease pathogenesis and test new therapies, but divergent outcomes have been observed with the same treatment even when using the same sepsis model. Other disorders such as diabetes, cancer, malaria, obesity, and cardiovascular diseases have used standardized, preclinical models that allow laboratories to compare results. Standardized models accelerate the pace of research and such models have been used to test new therapies or changes in treatment guidelines. The National Institutes of Health mandated that investigators increase data reproducibility and the rigor of scientific experiments and has also issued research funding announcements about the development and refinement of standardized models. Our premise is that refinement and standardization of preclinical sepsis models may accelerate the development and testing of potential therapeutics for human sepsis, as has been the case with preclinical models for other disorders. As a first step toward creating standardized models, we suggest standardizing the technical standards of the widely used cecal ligation and puncture model and creating a list of appropriate organ injury and immune dysfunction parameters. Standardized sepsis models could enhance reproducibility and allow comparison of results between laboratories and may accelerate our understanding of the pathogenesis of sepsis.